The Effect Of Giving Calcium As An Effort To Prevent Preeclampsia: A Literature Review - Desy Dwi Cahyani Cahyani; Ega Ayundasari; Heppy Rina Mardiana; Sunaeni Sunaeni; Irawati Irawati; Mulyati Mulyati (An Idea Nursing Journal, 2023)
Preeclampsia is a pregnancy disorder accompanied by hypertension and proteinuria. Efforts to prevent preeclampsia can be made with medical prevention, namely, meeting the calcium needs of pregnant women. This research aims to determine the effect of givingcalcium to prevent preeclampsia. The method used in the literature review is a systematic mapping study obtained from 3 databases, namely Pubmed, Garuda, and Google Scholar, using inclusion and exclusion criteria. Key term used in searching literature: "Calcium for prevention of preeclampsia." from 10 journals, it was found that the correct dose of calcium and timing of giving calcium to pregnant women was found and that calcium had an effect on preventing preeclampsia. Data analysis techniques use Synthesize or compare. Conclusion: Mothers are advised to consume calcium because it can lower blood pressure. By reducing blood pressure in pregnant women, calcium can prevent the occurrence of preeclampsia, especially in pregnant women who have hypertension or a history of preeclampsia.